Life Cycle Assessment of renewable filler material (biochar) produced from perennial grass (Miscanthus) - Debela Tadele; Poritosh Roy; Fantahun Defersha; Manjusri Misra; Amar K. Mohanty (AIMS Energy, 2019)
Biochar, a hydrophobic biomaterial produced from lignocellulosic biomass is a promising alternative to conventional filler materials. Although a variety of feedstocks have been analyzed for producing biomaterials to a limited extend, a complete LCA study of Miscanthus biochar is scarce. This study evaluates the life cycle of biochar produced from Miscanthus that is grown on the marginal land in Ontario, Canada. Life cycle environmental impacts are determined by using the SimaPro LCA software adopting the TRACI method. The global warming potential (GWP) of the life cycle of biochar is found to be 117.6 kg CO2eq/t. Miscanthus cultivation (93.0 kg CO2eq/t) is the main contributor in the life cycle of Miscanthus biochar followed by pyrolysis (23.3 kg CO2eq/t) and transportation (4.8 kg CO2eq/t). Miscanthus cultivation is also the main contributor to acidification potential and non-carcinogenic potential; however, transportation and pyrolysis are the hotspots in the case of eutrophication, smog and ecotoxicity, and carcinogenic potential, ozone depletion potential and fossil fuel depletion, respectively. The sensitivity analysis reveals that the environmental impacts decrease with an increase of Miscanthus yield. The study provides information on the life cycle environmental impacts of biomaterial which would facilitate in selecting environmentally favorable filler material to replace conventional filler materials to mitigate environmental impacts.